2019
DOI: 10.3390/molecules24163018
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly of Covalently Linked Porphyrin Dimers at the Solid–Liquid Interface

Abstract: The synthesis and surface self-assembly behavior of two types of metal-porphyrin dimers is described. The first dimer type consists of two porphyrins linked via a rigid conjugated spacer, and the second type has an alkyne linker, which allows rotation of the porphyrin moieties with respect to each other. The conjugated dimers were equipped with two copper or two manganese centers, while the flexible dimers allowed a modular built-up that also made the incorporation of two different metal centers possible. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…The fabrication of highly ordered and diversified morphologies of nano- and micro-structured optoelectronic materials is of great contemporaneous interest, especially for their applications in catalysis, sensing, solar energy conversion, and storage [ 1 , 2 , 3 , 4 , 5 , 6 ]. Among the various building blocks, porphyrins are attractive components for the construction of self-assembled nanomaterials with well-defined shapes and dimensions [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. Combination of porphyrins and other optoelectronic functional materials has been extensively studied to develop new nanohybrid systems which can intensify light-harvesting and charge-transfer functions [ 16 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…The fabrication of highly ordered and diversified morphologies of nano- and micro-structured optoelectronic materials is of great contemporaneous interest, especially for their applications in catalysis, sensing, solar energy conversion, and storage [ 1 , 2 , 3 , 4 , 5 , 6 ]. Among the various building blocks, porphyrins are attractive components for the construction of self-assembled nanomaterials with well-defined shapes and dimensions [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. Combination of porphyrins and other optoelectronic functional materials has been extensively studied to develop new nanohybrid systems which can intensify light-harvesting and charge-transfer functions [ 16 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Generally speaking, whether a supramolecular self-assembly structure is stably ordered or not depends on the solvent, the type of functional group, and the interaction force between molecules. These interactions are noncovalent forces, which include hydrogen bonding, π–π stacking effect, van der Waals interaction, metal–ligand coordination, and so on. Supramolecules are able to self-regulate and thus balance the forces between molecules and molecules, and molecules and substrates to reach the equilibrium state ultimately . The investigation on porphyrin assemblies through hydrogen bonding on a two-dimensional surface has become a hot topic of study. , Due to the selectivity and saturation of hydrogen bonding, an increasing number of research have reported that porphyrin with a carboxyl functional group interacts with other molecules by hydrogen bonding to form supramolecular nanostructures. ,,, …”
Section: Introductionmentioning
confidence: 99%
“…While similar π–π interactions could be expected for the aniline groups at the outside of the molecules, these groups were observed to self-assemble edge-on to the surface to enhance π–π interactions between adjacent aniline groups in a parallel displaced stacking. The edge-on orientation on the surface has been reported for molecules containing largely conjugated systems, such as porphyrins, 22 or other strong directional intermolecular interactions, such as hydrogen bonding. 23 However, the results obtained from these experiments show that a parallel displaced stacking of substituted aniline groups can be sufficient to act as directional intermolecular interactions in the SAMN and convert the aniline groups to an edge on-orientation.…”
mentioning
confidence: 98%